Tailored polities in the shadow of the state's hierarchy. The CLLD implementation and a future research agenda. Issue 4 (3rd April 2019) - Servillo, Loris
ABSTRACT: The paper provides a theoretical contribution to the multi-level governance debate, discussing the role of the policy instruments in tailoring polities for local development strategies. To this purpose, it examines the Community-Led Local Development (CLLD), a policy tool of the EU Cohesion Policy 2014–2020, which has generated more than 3000 local initiatives across the EU. An institutionalist perspective enables a reflection on the multi-level normative dimensions of these local initiatives. A combination of the post-functionalist governance theory, the soft space debate, state-theory and strategic-relational approach provides an interpretative framework to be deployed for a dedicated research agenda. The interpretative challenge is about whether the CLLD enables spatial-temporal fixes in which a deliberative polity pursues a spatial imaginary for an ad-hoc territory. The consequent analytical dimensions can be found in (a) the relationship between attendant ad-hoc polity, policy agenda, territorial design and societal processes; and (b) the meta-governance dimensions that locate the bottom-up constituency of this institutional technology in the shadow of state's hierarchy. An overview of the CLLD implementation across the EU provides evidence on the latter.